Experiences and perceptions of meals on wheels volunteers in providing nutritional care to older adults: A qualitative evidence synthesis - Christine Fitzgerald; Brenda Gabriela Muñoz González; Pedro Salinas Escárcega; Anne Griffin (PLoS ONE, 2025)
In the community, Meals on Wheels (MoW) programmes are instrumental in the delivery of meals to nutritionally vulnerable older adults. This qualitative evidence synthesis aimed to explore the perceptions and experiences among volunteers of MoW services of their role in supporting nutrition care. Scopus, PubMed, CINAHL, Web of Science, Embase, MEDLINE, and PsycINFO were searched employing qualitative data collection and analysis methods. Results were synthesized using Thomas and Harden’s three step approach for thematic synthesis. Three articles were included and two themes were identified: (1) complexity in coordinating MoW to ensure service delivery, and (2) the MoW volunteers’ perception of their role in providing nutrition care was eclipsed by the social element of their role. While MoW is pivotal to support older adults’ independence, challenges like staffing, funding constraints, and limited community awareness of the service persist. Volunteers’ express positivity but face concerns about time commitment and replacement recruitment. Exploring MoW volunteers’ broader roles in food insecurity is imperative to understand and address the complex dynamics of providing nutrition care and support to older adults.